School Inspection in Ibero-America: the case of Chile - Adolfo I. GONZÁLEZ BRITO (Aula, 2019)
In Chile, School Inspection is known as Educational Supervision and, in general, it has the same character as other Latin American countries, except for some differences related to their roles that have been dynamic over the time; the inspectors, called Supervisors, are State officials at an intermediate level. This article gives an overview of the historical evolution of Educational Supervision in Chile since 1965 to the present. Mainly in order to the paradigm that sustains its performance in order to educational policy and, specifically, in order to their roles in the school system.